2017
DOI: 10.5301/hipint.5000585
|View full text |Cite
|
Sign up to set email alerts
|

Which is the best bearing surface for primary total hip replacement? A New Zealand Joint Registry study

Abstract: CoPx remained the most durable and successful coupling used in primary THR in New Zealand irrespective of age, gender or size of femoral head.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
0
15
1
Order By: Relevance
“…Ceramic-on-HXLPE in primary THR has been shown to have the lowest all-cause revision rates in a large national joint registry study and the reduced wear evident with the use of vitamin E HXLPE may lead to further reduction in revision rates. 30 A reduction in revision rates has not been shown in this study.…”
Section: Discussioncontrasting
confidence: 54%
“…Ceramic-on-HXLPE in primary THR has been shown to have the lowest all-cause revision rates in a large national joint registry study and the reduced wear evident with the use of vitamin E HXLPE may lead to further reduction in revision rates. 30 A reduction in revision rates has not been shown in this study.…”
Section: Discussioncontrasting
confidence: 54%
“…Compared to traditional metal heads, ceramic femoral heads have a very low revision rate. A large-scale national joint registration analysis [ 33 ] indicated that lining ceramic heads with VE-PE may further reduce the revision rate. In our analysis, it was found that the revision rate of the VE-PE group was reduced by 46% (1-0.54) compared with that of the non-VE-PE group.…”
Section: Discussionmentioning
confidence: 99%
“…Bearing choice in the British group was mostly ceramic on ceramic, however in the Irish group ceramic on polyethylene was chosen by the majority of surgeons which is in line with current evidence on the least wear in bearing surfaces. [13, 14]…”
Section: Discussionmentioning
confidence: 99%